The Electric Susceptibility of Bi-Layers Ferroelectrics - Vincensius Gunawan; Ngurah Ayu Ketut Umiati; Agus Subagio (Journal of Physics and Its Applications, 2019)
In order to enhance insight of layered structure, we perform numerical calculation to obtain the dynamic electric susceptibility in bi-layers ferroelectrics. Since susceptibility is a parameter which gives response to the external field, then determination of this parameter is important. A lattice model is employed to slice bilayer structure into several lattices.  Then, Landau-Khalatnikov equation of motion is used in each lattice to construct a matrix equation of equation of motion.  The solution is obtained by applying entire-cell effective medium.  We find that the homogeneity of dynamic polarization is different from homogeneity of the single individual layer due to the existence of interlayer interaction.  As a result, the electric susceptibility is also altered.  It is also noticed that there is a relation between the homogeneity of dynamic polarization and the value of electric susceptibility near resonant frequency.  The higher the homogeneity, the bigger the values of susceptibility will be.